Effect of Application Rate on Gold Ore Extraction Process with Column Test Method at PT J Resources Bolaang Mongondow, North Sulawesi - Frederico Espinoza Rangan; Sudaryanto Sudaryanto (Journal of Metallurgical Engineering and Processing Technology, 2024)
PT J Resouces Bolaang Mongondow is engaged in gold processing with the heap leach process using the dynamic cell method. However, currently there will be a change to the static cell method so that it will affect the operational strategy including the application rate. Therefore, in this research, testwork was carried out to determine the best application rate to be used in the static cell process, studying the effect of application rate on leaching kinetics, percent gold extraction value, and cyanide consumption. The research stages include preparation and testing of head assay samples, leaching, and preparation and testing of tailings samples using the column test method. The application rate variations used were 20 L/m2 /h, a combination of 20 & 10 L/m2 /h, and 10 L/m2 /h. Pregnant leach solution obtained per day is checked for pH, free cyanide, and metal content analysis for the calculation of the percent extraction by back calculated. The results showed that the application rate of 20 L/m2 /h and the combination of 20 & 10 L/m2 /h had faster primary leaching kinetics than the application rate of 10 L/m2 /h. Analysis of the percent extraction of application rate 10 L/m2 /h has the highest percent extraction of 89% (0.2081 mg/L gold). Application rate also has an impact on cyanide consumption, where the application rate of 20 L/m2 /h has the highest cyanide consumption of 0.13 g/t. Meanwhile, the application rate combination of 20 & 10 L/m2 /h and 10 L/m2 /h had cyanide consumption of 0.081 g/t and 0.067 g/t, respectively. From the results, it is concluded that the best application rate is the combination of 20 & 10 L/m2 /h, judging from the leaching kinetics factor and the percent extraction obtained. On the other hand, the volume of solution produced is also less so that it can minimize the occurrence of landslides on the leach pad